Invisible Domestic Violences: How Parents did Emotional and Verbal Violences to their Children Unconsciously - Yusri, Yusri (Universitas Negeri Makassar, 2023)
This study aims to determine the forms of violence experienced by children at home and how parents understand violence. The research methodology used is quantitative through a survey approach. Research participants consisted of children (12-17 years old) and parents. Data collection techniques used are online surveys and interviews. The online survey was conducted for all participants consisting of 50 children and 50 parents. Meanwhile, the interviews were only conducted with a sample of parents. All respondents agreed to participate in this study through a verbal consent form. The data analysis technique used is descriptive statistics and qualitative descriptive. The findings of this study indicate that 1) parents still tend to commit various forms of violence against children such as physical violence, verbal violence, emotional violence, and neglect. This violent behavior is carried out for various reasons, both consciously and unconsciously. 2) Parents tend to understand that violence only consists of physical violence and verbal violence. 3) there is a relationship between parents' lack of understanding about violence and the potential for violence perpetrated by parents against children. This study also recommends that it is important to conduct interventions for parents that focus on increasing parents' understanding of the types of violence and the negative impacts caused as a form of preventing domestic violence.